1998
DOI: 10.1093/humrep/13.suppl_1.165
|View full text |Cite
|
Sign up to set email alerts
|

Survey on intracytoplasmic sperm injection: report from the ESHRE ICSI Task Force

Abstract: Intracytoplasmic sperm injection (ICSI) has revolutionized the treatment of male infertility, since normal fertilization and ongoing pregnancies can be achieved with severely affected spermatozoa. Hence, the application of ICSI is rapidly expanding around the world, necessitating an accurate assessment of the efficacy and safety of this novel technique. The European Society of Human Reproduction and Embryology (ESHRE) Task Force is gathering data annually on the clinical results, the pregnancy outcome and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 19 publications
0
31
0
3
Order By: Relevance
“…These included the annual reports from the large national registry maintained by the Society for Assisted Reproductive Technology in cooperation with the Centers for Disease Control in the United States and the Multi-National Cooperative Registry, operated through the European Society for Human Reproduction and Endocrinology. (26,27) From the 44 controlled studies retrieved for close analysis, we excluded studies without ascertainable control groups, studies which did not report malformations as an outcome, and studies which combined MM and minor malformations in a single metric.…”
Section: Methodsmentioning
confidence: 99%
“…These included the annual reports from the large national registry maintained by the Society for Assisted Reproductive Technology in cooperation with the Centers for Disease Control in the United States and the Multi-National Cooperative Registry, operated through the European Society for Human Reproduction and Endocrinology. (26,27) From the 44 controlled studies retrieved for close analysis, we excluded studies without ascertainable control groups, studies which did not report malformations as an outcome, and studies which combined MM and minor malformations in a single metric.…”
Section: Methodsmentioning
confidence: 99%
“…This is of particular relevance in view of the potential effect that these abnormalities may have on ICSI offspring. The increase risk of inherited chromosomal abnormalities is now well-documented from both studies using retrospectively matched controls (Tarlatzis and Bili, 1998;Bonduelle et al, 1998) and a prospective controlled study (Aboulghar et al, 2001). However, Bonduelle et al demonstrated an increase not only in inherited (0.92 versus 0.47%), but also de-novo (1.66 versus 0.44%), abnormalities of which half were sex chromosomal (0.83 versus 0.19%).…”
Section: Introductionmentioning
confidence: 99%
“…However, in a large comparative study in 2000 Wennerholm et al, [101] compared ICSI births with IVF births and found no increase in major malformations between these two groups, concluding that this increased rate of congenital malformations is not associated with sperm origin or quality but rather due to a higher rate of multiple births. In 1998, the European Society Human Fertilization and Embryology ICSI Task Force confirmed the findings of smaller studies, reporting an increased risk (2%) of chromosomal abnormalities in ICSI babies [87].…”
Section: Follow Up Of Babies Conceived By Icsimentioning
confidence: 82%
“…The next major study was conducted by the International collaborative study of ICSI child and family outcomes group over a five year period [87] and no differences in cognitive, neurological or socio-economic development were observed although they highlighted an increase in urogenital problems in males more recently. In 2004 a meta-analysis [68] found compared major malformations rates ranged from 1.1-9.7% in ICSI compared with 0-6.9% in spontaneously conceived infants.…”
Section: Follow Up Of Babies Conceived By Icsimentioning
confidence: 99%